Superior Capsular Reconstruction: Fascia Lata Versus Acellular Dermal Allograft: A Systematic Review - Amr Ahmed Abd Elrahman, M.D; Mohamed Hassan Sobhy, M.D; Haytham Abdelazim, M.D; Haitham Kamel Omar Haroun, M.D (Elsevier, 2020)
Purpose: We systematically reviewed the literature to compare the clinical and radiologic outcomes and retear rates of superior capsular reconstruction (SCR) using fascia lata autograft (FLA) versus human dermal allograft (HDA) in cases of massive irreparable rotator cuff tears. Methods: Searches of Pub Med and Cochrane Library identified clinical studies addressing SCR using FLA and HDA. Two reviewers independently screened the titles, abstracts and full texts to extract data from eligible studies. Reported outcome measures were descriptively analyzed. Results: A total of 6 studies with 2 study groups satisfied the inclusion criteria. The number of shoulders in the HDA group was 155, and in the FLA group, the number was 140 shoulders. The mean age at time of surgery for the HDA group and the FLA group was 60.49 years and 65.8 years, respectively, and the mean follow-up was 15.2 months and 44.6 months, respectively. Active elevation improved from of 121°-130° to 158°-160° in the HDA group and from 74.8°-133° to 130.4°-146° in the FLA group. Active external rotation improved from 36°-45° in the HDA group and from 13°-28° to 30°-43° in the FLA group. The Visual Analog Scale for pain improved from 4-6.25 to 0.38-1.7 points in the HDA group, whereas in the FLA group, it improved from 6-2.5 points. In the HDA group, American Shoulder and Elbow Surgeons scores improved from 42-52 to 77.5-86.5, whereas in the FLA group scores improved from 35-54.4 to 73.7-94.3. The acromiohumeral distance improved in both groups. The retear rate was 3.4%-55% in the HDA group and 4.5%-29% % in the FLA group. Conclusions: Arthroscopic SCR for massive, irreparable rotator cuff tears using both fascia lata allograft and human dermal allograft leads to improvement in clinical outcomes and radiologic outcomes. There is a lower retear rate in fascia lata allografts. The current literature is heterogeneous and has low levels of evidence. Level of Evidence: Level IV, systematic review of level IV studies.